Multiwavelength properties of 850-μm selected sources from the North Ecliptic Pole SCUBA-2 survey. Issue 2 (25th April 2022) - Shim, Hyunjin; Lee, Dongseob; Kim, Yeonsik; Scott, Douglas; Serjeant, Stephen; Ao, Yiping; Barrufet, Laia; Chapman, Scott C; Clements, David L; Conselice, Christopher J; Goto, Tomotsugu; Greve, Thomas R; et al.
ABSTRACT: We present the multiwavelength counterparts of 850-μ m selected submillimetre sources over a 2-deg 2 field centred on the North Ecliptic Pole. In order to overcome the large beam size (15 arcsec) of the 850-μ m images, deep optical to near-infrared (NIR) photometric data and arcsecond-resolution 20-cm images are used to identify counterparts of submillimetre sources. Among 647 sources, we identify 514 reliable counterparts for 449 sources (69 per cent in number), based either on probabilities of chance associations calculated from positional offsets or offsets combined with the optical-to-NIR colours. In the radio imaging, the fraction of 850-μ m sources having multiple counterparts is 7 per cent. The photometric redshift, infrared luminosity, stellar mass, star formation rate (SFR), and the active galactic nucleus (AGN) contribution to the total infrared luminosity of the identified counterparts are investigated through spectral energy distribution fitting. The SMGs are infrared-luminous galaxies at an average 〈 z 〉 = 2.5 with log10 ( L IR /L⊙ ) = 11.5–13.5, with a mean stellar mass of log10 ( M star /M⊙ ) = 10.90 and SFR of log_10 (SFR/M_ yr^-1)=2.34 . The submillimetre galaxies (SMGs) show twice as large SFR as galaxies on the star-forming main sequence, and about 40 per cent of the SMGs are classified as objects with bursty star formation. At z ≥ 4, the contribution of AGN luminosity to total luminosity for most SMGs is larger than 30 per cent. The FIR-to-radio correlation coefficient of SMGs is consistent with that of main-sequence galaxies at z ≃ 2.